Unilateral and bilateral load-velocity relationships in athletes: evidence from a study in boxers - Han, Yemin; Xie, Yiqing; Niu, Zhen; Jia, Jiawang; Zhang, Zhen (Frontiers in Sports and Active Living, 2025)
ObjectiveThis study aimed to investigate the load-velocity (L-V) relationship in boxers during unilateral (Bulgarian split-squat, BSS) and bilateral (back-squat, BS) lower-limb exercises, and to compare the mean velocity (MV) outputs between these two modalities, with the ultimate goal of providing an evidence-based foundation for optimizing strength training in boxing.MethodsTwenty trained boxers (age: 19.7 ± 1.0 years) performed incremental loading tests on a Smith machine equipped with a linear position transducer (GymAware) to record MV. Unilateral testing was performed on each leg in a randomized order, with loading progressed incrementally from 30% to 100% of the predicted one repetition maximum (1RM). Participants performed three repetitions at 30%–70% predicted 1RM, two repetitions at 75%–90% predicted 1RM, and one repetition at 95%–100% predicted 1RM, with a 10-second rest between repetitions and a 5-minute rest between load conditions.ResultsWe found a close relationship between MV and relative load (%1RM) in both BSS and BS exercises for the non-dominant legs (coefficient of determination; R2 = 0.94, standard error of estimate; SEE = 0.05 m·s−1), dominant legs (R2 = 0.94, SEE = 0.05 m·s−1), and back-squat (R2 = 0.95, SEE = 0.05 m·s−1), reflecting a nearly perfect relationship as per standard interpretations of coefficient strength. Compared to Bulgarian split-squat, back-squat exhibited significantly higher MV at the same %1RM (P < 0.01, η² = 0.256).ConclusionThis study validated the use of velocity-based resistance training (VBT) to optimize strength training in boxing. Both unilateral and bilateral exercises showed consistent L-V relationships, supporting individualized load prescription. Bilateral exercises enhanced velocity output, while unilateral exercises helped correct inter-limb strength asymmetries and improve sport-specific stability.